"Water sector reforms" - A framework for collective action (Note) - Arun Kumar (2002)
An enabling environment for ushering in water sector reforms has been conceived in the present article. It opens the discussion with a brief outline of National Water Policy, captures some of the most salient features of Indian water scenario and then presents us with policy options in undertaking a multi-dimensional reforms process ranging from Participatory Irrigation Management to Integrated Water Resource Management to institutional reorganisation of irrigation agencies to adoption of new techniques and technology. - Reproduced.
Keywords: Note; Social programmes; Water resources management